"Sore eyes and distracted" or "excited and confident"? – The role of perceived negative consequences of using ICT for perceived usefulness and self-efficacy. (December 2017) - Scherer, Ronny; Hatlevik, Ove E.
Abstract: Many adolescents feel confident about using information and communication technology (ICT) and believe that it can help them to learn and achieve. However, recent research also shows that some adolescents are reporting physical discomfort from using ICT such as sore eyes and pain in neck and shoulders. This paper explores how primary school students perceive the negative consequences of using ICT (i.e., discomfort and distraction) in relation to the use of ICT for school and leisure purposes, their self-beliefs, and the perceived usefulness of ICT. Using the data obtained from a large sample of Norwegian seventh-graders ( N = 1, 640, between 12 and 13 years old), we performed structural equation modelling to test our assumptions on the role of students' discomfort from using ICT. We hypothesized an indirect effects model, in which the use of ICT and students' beliefs are indirectly associated via perceived discomfort. Our findings are two-fold: First, discomfort from using ICT was negatively related to students' use of ICT for leisure; yet neither to self-efficacy in using ICT nor perceived usefulness. In contrast, perceived distraction by ICT was negatively related to perceived usefulness, yet positively associated with ICT use in lessons. Second, the direct and positive relations among the use of ICT, perceived usefulness, and self-efficacy were statistically significant. These findings uncover that the potentially negative consequences of distraction relate to the extent to which students perceive ICT as useful. Highlights: Discomfort and distraction are perceived negative consequences of ICT. Perceived usefulness and ICT self-efficacy are positive outcomes of ICT. Perceived discomfort and distraction by ICT go together. ICT distraction is related to less positive perceptions of the usefulness of ICT.